تأثیر الخصائص الاجتماعیة_الاقتصادیة فی نموذج تولد الرحلاتمنطقة الدراسة ( التأمیم و5 کیلو) باستخدام الانحدار الخطی المتعدد - nan, nan (Iraqi Journal of Civil Engineering, 2010)
The first step toward urban transportation planning is to make a data base then to initiate the first mathematical model known as trip generation model which this study adopts. The study area in the waste sector of Ramadi city (Al-Tameem, 5 km) is considered as one sector consists of eight zones containing about 11640 dwelling units. Home interview survey was made of random sample which represent 5% of the study area population. The collected information was concerned with structure, vehicles, families and each person living in the dwelling unit. The total person’s trips per dwelling unit and various purposes were investigated. All data was programmed for analysis by spss program, which took place firstly by multiple linear regression to obtain the primarily models. After series of analysis and trials, the most significant independent variables were identified as family size and car ownership. Also, the final equations for producing trips were obtained. They were reasonable, more practical and carrying the best statistical measures. Set of curves were developed to put the sub models in any easy and more desirable manner for wide application and forecasting.